Ulysses Kay Special Collection: Rare Book and Manuscript Library, Columbia University - Lee, Jennifer (Current Musicology, 2012)
African–American composer Ulysses Kay (1917–1995) wrote more than one hundred forty compositions in a wide range of forms—five operas, over twenty large orchestral works, more than thirty choral compositions, fifteen chamber works, a ballet, and numerous other compositions for voice, solo instruments, film, and television. Born in Tucson, Arizona to a musical family, Kay was encouraged by both his mother and her brother, Joe “King” Oliver, to study piano, violin and saxophone. He entered the University of Arizona in 1934, receiving the Bachelor of Music in 1938. For the next two years he studied composition at the Eastman School of Music, University of Rochester, with Bernard Rogers and Howard Hanson, and received the Masters in Music in 1940. From 1941 to 1942 he studied with Paul Hindemith at Tanglewood and at Yale University. Compositions from this period include the “Sinfonietta for Orchestra,” the ballet “Danse Calinda,” and “Three Fanfares for Four Trumpets.”